Surgical Procedure for Pyometra and Mammae Tumor Treatment in a Pitbull Dog - Rickyawan, Nofan; Virgiantari, Cheptien Winda; Lesmana, Muhamad Arfan; Vidiastuti, Dian (Universitas Airlangga, 2022)
Pyometra is an infection or inflammation of the uterine wall characterized by the accumulation of pus in the uterine lumen. Predisposing factors include age, breed, bacterial infection, and hormones. Another disease that is often correlated with an imbalance in reproductive hormones is mammary tumors. A 7-year-old unspayed female Pitbull dog weighed 27.9 kg has clinical symptoms of frequent discharge of mucopurulent reddish-brown discharge with a foul odor from the vagina. The left mammary glands of the second, third, and fourth nipples have lumps about 20 cm in diameter, are solid in consistency, well-defined, the same color as the skin surface, and can be moved. Diagnosis performed on physical examination, hematology, blood chemistry, and cytology was pyometra and mammary tumors. Treatment was done by ovariohysterectomy and unilateral mastectomy. Post-surgery therapy was enrofloxacin 5 mg/kg, ketoprofen 2 mg/kg, phytomenadione 1 mg/kg, and Biodin® 0.1 ml/kg, followed by intensive surgical wound care. The patient recovered after two months of treatment.